Long‐term efficacy and safety of radiofrequency catheter ablation of atrial fibrillation in patients with cardiac implantable electronic devices and transvenous leads. (10th March 2019) - Dinshaw, Leon; Schäffer, Benjamin; Akbulak, Özge; Jularic, Mario; Hartmann, Jens; Klatt, Niklas; Dickow, Jannis; Gunawardene, Melanie; Münkler, Paula; Hakmi, Samer; Pecha, Simon; Sultan, Arian; et al.
Abstract: Introduction: Long‐term efficacy and safety are uncertain in patients with cardiac implantable electronic devices (CIED) and transvenous leads (TVL) undergoing radiofrequency catheter ablation of atrial fibrillation (AF). Thus, we assessed the outcome of AF ablation in those patients during long‐term follow‐up using continuous atrial rhythm monitoring (CARM). Methods and Results: A total of 190 patients (71.3 ± 10.7 years; 108 (56.8% men) were included in this study. At index procedure 81 (42.6%) patients presented with paroxysmal AF and 109 (57.4%) with persistent AF. The ablation strategy included pulmonary vein isolation in all patients and biatrial ablation of complex fractionated electrograms with additional ablation lines, if appropriate. AF recurrences were assessed by CARM‐ and CIED‐related complications by device follow‐up. After a mean follow‐up of 55.4 ± 38.1 months, freedom of AF was found in 86 (61.4%) and clinical success defined as an AF burden less than or equal to 1% in 101 (72.1%) patients. Freedom of AF was reported in 74.6% and 51.9% ( P = 0.006) and clinical success in 89.8% and 59.3% ( P < 0.001) of patients with paroxysmal and persistent AF, respectively. In 3 of 408 (0.7%) ablation procedures, a TVL malfunction occurred within 90 days after catheter ablation. During long‐term follow‐up 9 (4.7%) patients showed lead dislodgement, 2 (1.1%) lead fracture, and 2 (1.1%) lead insulation defect not related to the ablation procedure. Conclusion: Our findings using CARM demonstrate long‐term efficacy and safety of radiofrequency catheter ablation of AF in patients with CIED and TVL.